Analisis Peraturan Daerah Kabupaten Buleleng Nomor 3 Tahun 2018 Tentang Perubahan Atas Peraturan Daerah Kabupaten Buleleng Nomor 10 Tahun 2011 Tentang Pajak Hiburan - Sella Marsellena Mercury (Universitas Pendidikan Ganesha, 2021)
Indonesia is a constitusional state as stated in the 1945 Constitution Article 1 Paragraph 3. So that vaious things exist in state govermened by applicable law, including in this case is tax. There are various types of taxes in Indonesia. One of them is local taxes. Law number 34 year 2000, this law stipulates that there are 11 regional taxes, including 4 (four) provincial taxes and 7 (seven) types of regency or city taxes. District or city taxes include hotel tax, entertainment tax, adventisement tax, street lightning tax, restaurant tax, parking tax, and class C mineral ectraction tax. So when talking about entertainment tax, it is included in regency tax in Buleleng Regency, entertainment tax is regulated in Buleleng Regency. Regional Regulation No. 3 of 2018 concerning Amendments to the Buleleng Regency Regional Regulation Number 10 of 2011 concerning entertainment tax. This type of research the writer uses is legal research (yudicial) which is normative in ature. The approach used in this study is the statue approach, conceptual approach, legalhistory ap proach, and the case approach. Buleleng Regency Regional Regulation Number 3 of 2018 in fact does not have a significant differences with the previous regional regulations interest and welfare of the community.